Desenvolvimento de monolitos poliméricos porosos a base de acetato de celulose para remoção de contaminantes em efluentes: estudo de remoção de cristal violeta - Ricci, Poliana (2023)
Monoliths are unique pieces formed by a hierarchically interconnected three-dimensional porous structure. These materials can be employed in separation and extraction processes of environmentally, pharmacologically, and/or biologically relevant compounds. In this study, cellulose acetate (CA) was used in the production of monoliths through thermally induced nonsolvent phase separation (TINIPS). To better understand the processes leading to monolith formation, solutions of CA in Dimethylformamide (DMF) were studied in the presence of nonsolvents: n-butanol, n-hexanol, and n-octanol. Based on these studies, monoliths were prepared from the formulations: DMF/Butanol (MCAB) at 1.0/1.5 (v/v), DMF/Hexanol (MCAH), and DMF/Octanol (MCAO) at a ratio of 1.0/1.0 (v/v). The solutions were cooled and kept at rest for about two weeks to form the gel, followed by solvent exchange and drying to form the monoliths. The monoliths were characterized using FTIR, TGA, DSC, DR-X, ASAP, SEM, and porosity measurements. The monoliths exhibited differences in some properties compared to CA, such as an increase in total porosity, which effectively influenced the thermal properties. The increased porosity was confirmed by measurements of macroporosity, SEM images, and analysis of surface area and porosity. The SEM images revealed the porous structure of the monoliths, with MCAO displaying an open structure, while MCAH and MCAB exhibited a spongy and globular porous structure, respectively. The differences in morphologies were attributed to the carbon chain size of the alcohol and differences in the polymer solution demixing rate. MCAH and MCAO monoliths showed a surface area of 73 m² g⁻¹ and 1.430 m² g⁻¹, with an average pore diameter ranging from 2 nm to 50 nm, indicating the presence of mesopores. The MCAO monolith was selected for adsorption/desorption studies of the crystal violet (CV) dye. The monoliths readily adsorbed CV, with a moderate maximum adsorption capacity (qe), possibly dependent on the modulation of the monolith's porous hierarchy, considering the presence of micro and mesopores. In desorption tests of CV for monolith recovery after adsorption cycles, various solvent extractors for CV were tested, including ethanol, methanol, pH 2, and pH 9 solutions, with good results obtained for ethanol and methanol solvents. Thus, it is concluded that the proposal to develop a hierarchically porous CA-based structure for the extraction of the CV dye demonstrated effective and promising results for further applications such as extraction, reactors, immobilization, ion exchange, catalysis and sensors.